Charging history and fluid evolution for the Carboniferous volcanic reservoirs in the western Chepaizi Uplift of Junggar Basin as determined by fluid inclusions and basin modelling. (21st May 2019) - Shi, Bingbing; Chang, Xiangchun; Xu, Youde; Mao, Lixin; Zhang, Jianhua; Li, Yang
Abstract : Fluid inclusions are rich in the Carboniferous volcanic reservoirs in the western Chepaizi Uplift, occurring in liquid, gaseous, and gas–liquid phases. In this study, the fluid inclusions were investigated in terms of petrographic, optical, and microthermometric characteristics, coupled with pressure–volume–temperature–composition (PVTX) simulations. Two periods of hydrothermal activities in the Carboniferous volcanic reservoirs were suggested by the bimodal distributions of Th (homogenization temperatures) of fluid inclusions with 120–140°C and 160–190°C as the main peaks. The early charged fluids were characterized by a low temperature, low salinity, relatively higher density, and low G/L (gas–liquid volumetric ratio) of aqueous inclusions, whilst the late charged fluids featured a high temperature, moderate salinity, moderate density, and high G/L of aqueous inclusions. The oil inclusions hosted in calcite or quartz veins exhibited light yellow and yellowish‐green fluorescence, whereas those in the microcracks cutting or within quartz or calcite veins showed blue‐white fluorescence. The burial and geothermal histories imply an existence of abnormal hydrothermal activity under overpressure and high temperature, which is evidenced by the simulated trapping pressure that is higher than the lithostatic pressure and the measured Th values that are higher than the formation paleo‐temperatures. The Th range is widely and continuously distributed and, in combination with the burial history, indicates that the hydrocarbon accumulation in the research area has been a continuous process since the Paleogene. Combined with the reconstruction of tectonic evolution and hydrocarbon generation and expulsion, two oil‐charging episodes were defined, that is, the Late Oligocene–Early Miocene (23–16 Ma) and the Late Miocene–Holocene (6 Ma–). The western section of the Aika Fault Belt (F2 ), together with the sheet sandbodies of the Toutunhe Formation (J2 t), and the unconformities between Carboniferous–Cretaceous may have served as the migration pathways.